CRIME VICTIM COMPENSATION - Aleksandrovich Ivanov, Dmitriy; Sergeevna Esina, Alla; Vladimirovich Fadeev, Pavel; Georgievna Chasovnikova, Olga; Andreevna Zorina, Elena (Gênero & Direito, 2020)
this article aims to study international legal instruments that govern the compensation for crime victims in particular countries. In addition, the study aims to conduct a comparative analysis of different approaches to crime victims’ compensation stipulated in the legislation of foreign countries. The obtained results help conclude that approaches to compensation should be improved to comply with modern requirements and compensation methods.